ANALISIS NILAI KEBUDAYAAN DAN UNSUR KEBAHASAAN DALAM PUJIAN â€œSEMBAHYANGâ€ - Hardiana, Maulidia Tifani Alfin Nur (University of Brawijaya, 2021)
This study aims to 1) analyze the value of culture; and 2) analyze linguistic elements in praise of